(untitled) (The Journal of Psychology and Sociology, 2017)
This article is devoted to the prospects of the transition of traditional energy sources to the future renewed energy. The purpose of the work is to explain the advantages of renewable energy sources – solar energy, wind and hydropower over traditional sources – oil, gas, coal. New sources of energy have a beneficial effect on improving human health. People should correctly understand new problems. These are the tasks of energizing the socialization of young people. The methodology of the study is the works of the founders of industrialization – D. Bella, I. Druker and E. Toffler. Methodologies for the development and use of clean energy sources in the Republic of Kazakhstan are dealt with by scientists. Scientists are working in depth on the use of wind and solar energy. At the international exhibition EXPO 2017 they will present their developments in this direction. This, for example, new technologies for the use of wind energy. The mechanisms developed by Kazakh scientists differ in principle from European ones: they do not involve propellers, but internal closed units. In sociology, three points of view on the periodization of the industrial revolution – D. Bella, I. Druker and E. Toffler – spread. The main criterion in them is the development of industrial technologies, and the industrial revolution is seen as a global process of turning manual labor into machine production. In particular, the American sociologist D. Bell singled out three stages. The main results and conclusions of the research work are to use the republic’s capabilities to build solar, wind and hydroelectric power stations. The maximum use of sunny days, the Dzungar Gates and the rivers of Kazakhstan. It will be much cheaper and environmentally friendly energy sources. The rationale for choosing the topic, its relevance is explained by the choice of the topic based on the experience of previous EXPO organizations in other countries, especially Italy (Milan). The relevance of the topic is determined by the common interest in renewable energy sources. The object of research is renewable energy sources. The subject of research is the methods of realizing clean energy sources in practice. The purpose of the study is related to the proof of the thesis that the renewable energy sources are much cheaper and environmentally cleaner, Have a beneficial effect on human health than coal, oil, gas as energy sources. Hypotheses can be that with the use of new sources of enregis can get rid of the severe types of human diseases. The methods of research in this case are content analysis and observation, and Gutman’s indicators and scales became measures of effectiveness. Thus the validity of the research, as well as the addiction, are provided. Key words: solar energy, wind energy, hydropower, future energy, industrial revolution.